Oxidative Stress-Induced Diseases via the ASK1 Signaling Pathway - Mayumi Soga; Atsushi Matsuzawa; Hidenori Ichijo (International Journal of Cell Biology)
Apoptosis signal-regulating kinase 1 (ASK1) is a mitogen-activated protein kinase (MAPK) kinase kinase that activates the downstream MAPKs, c-Jun N-terminal kinase (JNK) and p38. ASK1 is activated by various types of stress, such as oxidative stress, endoplasmic reticulum stress, and infection, and regulates various cellular functions. Recently, it has been reported that ASK1 is associated with various diseases induced by oxidative stress. In this review, we introduce recent findings of the regulatory mechanisms of ASK1 and the oxidative stress-induced diseases mediated by the ASK1 signaling pathway.